Cannabis Use in Opioid Maintenance Therapy: Prevalence, Clinical Correlates and Reasons for Use - Markus Backmund; Greta G. Zámbó; Susanne Schöfl; Michael Soyka (Brain Sciences)
Background and aims: Opioid maintenance therapy (OMT) is the first-line treatment for opioid use disorder (OUD), reducing opioid use and mortality while improving physical and mental health. However, concomitant substance use remains common, with cannabis being the most frequently used substance. This study assessed the prevalence and clinical correlates of cannabis use in OMT patients, as well as individual motivations. Methods: In this cross-sectional, single-center study, 128 OUD patients (96 male, 32 female) receiving OMT were assessed using standardized questionnaires: the Marijuana Smoking History Questionnaire (MSHQ), Cannabis Problems Questionnaire (CPQ) and the Severity of Dependence Scale (SDS). Cannabis users and non-users were compared regarding type (methadone vs. buprenorphine) and dosage of maintenance medication. Results: Cannabis use was reported by 41% of patients, 73% met criteria for cannabis dependence, 30% of the full sample. Of the patients, 85% reported cannabis-related legal issues. Common reasons for use included recreational motives (mood change, enhancement) and reduction in cravings for other substances. Cannabis dependence was significantly more common in patients receiving buprenorphine than methadone. Higher methadone doses were also associated with increased cannabis use. These results suggest a clinically relevant pattern. Conclusions: Cannabis use is highly prevalent and appears to be influenced by type and dosage of substitution medication. These findings highlight a complex interaction between opioid treatment and cannabis use, possibly involving behavioral coping or regulatory processes. Further longitudinal and placebo-controlled trials are needed to investigate the clinical and pharmacological interactions between cannabis and OMT, including effects on craving, withdrawal, and overall treatment outcomes.